Effect of Squat Exercises on Fatigue and Quality of Life of Pregnant Women: A Randomized Controlled Trial Study - Maryam Malmir; Seyedeh Zahra Masoumi; Farideh Kazemi; Mansoureh Refaei (Guilan University of Medical Sciences, 2022)
Introduction: Research has shown that many pregnant women in Iran do not exercise during pregnancy. However, exercise, especially endurance exercise during pregnancy, is associated with good maternal and fetal outcomes. Objective: The study aimed to examine the effect of squat exercises on fatigue and the life quality of pregnant women admitted to health centers in Hamadan City, Iran. Materials and Methods: The study was a randomized controlled clinical trial conducted from September 2019 to February 2020 on 100 pregnant women in two groups of 50 each. The pregnant women were randomly using blocks of four divided into two groups according to the inclusion criteria. The samples filled out the fatigue questionnaire multidimensional symptoms fatigue inventory-short form (MSFI-SF) and SF-36 life quality questionnaire at the beginning of the study. Eight group sports sessions were held for women in the intervention group, and routine care was administered to the control group. The obtained data were analyzed using the independent t test, Mann-Whitney U test, Chi-square test, and analysis of covariance (ANCOVA) at a significance level of 0.05. Results: The mean ± SD age of participants was 28.24 ± 5.39 years in the intervention group and 27.78 ± 5.58 years in the control group. The mean scores of fatigue and life quality in all dimensions in the post-intervention stage (after adjusting for before-the-intervention scores, income, and housing status) were significantly different between the study groups. The mean fatigue score in the intervention group was lower, and the quality of life was better (P=0.001) than in the control group. The effect size of different domains of quality of life varied from 1.51 (energy fatigue) to 3.50 (physical function). The effect size of fatigue was 2.81 (95%CI: 3.36- 2.25, P=0.001). Conclusion: Based on the results, squat exercises are recommended to reduce fatigue and increase the life quality of pregnant women in health centers.